Who was Juliette Gordon Low? - Rau, Dana Meachen, 1971-; Putra, Dede (Illustrator) (New York : Penguin Workshop, 2021)
"Born in 1860 in Savannah, Georgia, Juliette Gordon Low grew up having the finest clothes and education. She was expected to be a prim and proper lady, but "Crazy Daisy"--as she was nicknamed by her friends and family--preferred to climb trees, ride horses, and hike. She also tried to find ways to help people in need. She carried that caring spirit with her into adulthood and used it to develop the Girl Scouts of the United States of America in 1912. Today, Juliette's organization continues to empower young girls, improve their self-esteem, and provide them with lifelong skills and a community of sisterhood"
Timelines.
Includes bibliographical references (pages 106-107).
Keywords: Low, Juliette Gordon, -- 1860-1927 -- Juvenile literature; Girl Scouts of the United States of America -- History -- Juvenile literature; Biographies